THE INFLUENCE OF ORGANIZATIONAL CLIMATE AND WORK MOTIVATION ON THE PERFORMANCE OF EMPLOYEES OF THE PLANNING AND ORGANIZATIONAL BUREAU OF THE GENERAL ELECTION COMMISSION OF THE REPUBLIC OF INDONESIA - Ardian Putra, Irwan; Sudarman , Enjang; Sembada, Gada (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
This study aims to determine the influence of organizational climate and work motivation on employee performance at the Planning and Organization Bureau of the General Election Commission of the Republic of Indonesia. The phenomenon underlying this study is the discovery of employees with suboptimal performance levels. In this study the author used quantitative research. The population in this study was 86 employees of the Planning and Organization Bureau of the General Election Commission of the Republic of Indonesia. In this study the author used a saturated sampling technique found in Non-Probability Sampling, a total of 86 employees. Data were collected using a closed questionnaire with a Likert scale, and analyzed using multiple linear regression with the help of the SPSS program version 20. The results of the study indicate that partially and simultaneously, the influence of organizational climate and work motivation has a positive and significant effect on employee performance. This study emphasizes the importance of the internal work atmosphere and providing motivation as a strategy to improve performance.